Prognostic Factors for the Occurrence of Recurrent Major Adverse Cardiac Events after Isolated Coronary Arterial Bypass Graft - Lim, Hendyono; Azzahra Maheswari Noersamsjah; Andry Irawan (HM Publisher, 2024)
Background: Coronary heart disease (CHD), commonly known as coronary artery disease (CAD), is a heart disorder that occurs when the arteries supplying blood to the heart walls experience hardening and narrowing, leading to a reduced supply of oxygen and nutrients to the myocardial tissue due to limited coronary blood flow. The treatment of CHD requires revascularization or reperfusion procedures on the coronary blood vessels responsible for supplying the heart muscle. One recommended therapy is coronary artery bypass grafting (CABG). Patients post-CABG are at risk of experiencing major adverse cardiovascular events (MACE). Methods: This design is a cross-sectional study involving all patients who underwent CABG at Siloam Hospitals in Lippo Village and Kebon Jeruk from January to June 2023. Data analysis using a regression approach aims to evaluate the relationship between various prognostic factors and MACE occurrences, thereby identifying a cross-sectional association between these variables and MACE events. Results: Findings from this cross-sectional study indicate a correlation between overweight and the occurrence of recurrent MACE in patients with a history of CABG (p-value = 0.037). These results suggest that individuals with obesity undergoing CABG have a higher risk of experiencing recurrent MACE in CHD. Conclusion: The prognostic factor for recurrent CHD-related major adverse cardiovascular events (MACE) is body mass index (BMI). Monitoring body mass index (BMI) in CHD patients who have undergone CABG is essential to reduce the risk of recurring MACE in the future.